TO THE QUESTION ABOUT SOURCES OF DIPLOMATIC RELATIONS BETWEEN THE REPUBLIC OF KAZAKHSTAN AND USA - Z.K. Ayupova; D.U. Kussainov (Academic Journal of Physical and Chemical Sciences, 2019)
It should be noted that the bilateral Kazakh-American partnership is part of the geostrategic and national interests of the United States not only in Kazakhstan, but also in the entire Central Asian region. However, it is Kazakhstan that is the most reliable partner of the United States in Central Asia, as Kazakhstan is politically stable, has significant economic potential, huge reserves of mineral resources, qualified technical personnel. Therefore, a certain political and economic presence of the United States in the center of the Eurasian continent is important for maintaining the geopolitical balance, stability, security, and prosperity of the region. During the first decade of independent development, Kazakhstan became open to the United States in political, economic, environmental, cultural and educational areas. Every year, various American senators visited our country, meeting both with government and with the public. United States in their faces looked like a great country, deserving of attention by its good example in building a market economy and a democratic society. The relationship between the two States is a strategic partnership. This applies not only to the economy, but also to the achievement of common global security objectives.